Jonathan Swift's Gulliver's travels : an annotated text with critical eassays - Swift, Jonathan; Bloom, Harold (New York : W.W. Norton, 2010)
Lemuel Gulliver always dreamed of sailing across the seas, but he never could have imagined the places his travels would take him. His adventures could be the greatest tales ever told, if he survives to tell them.
includes index.
"010-014 RL: 3.2; Guided reading level: L"--p. [4] of cover.
A Junior Library Guild selection
Keywords: Sailing -- Comic books, strips, etc. -- Juvenile fiction; Sailing -- Fiction; Cartoons and comics; Voyages, Imaginary; Satire; Children's stories -- Comic books, strips, etc